Short-Term Effects of Pre/Probiotics on P-Cresol and Indoxyl-Sulphate Serum Concentrations During the Various Stages of Chronic Kidney Disease - Filomena Panza; Diletta Duranti; Ralli Chiara; Matteo Basile; Marco Bagnati; Giorgio Bellomo; Ennio Duranti (Archives of Renal Diseases and Management - Peertechz Publications, 2017)
Background:The  uremic  syndrome  is  provoked  by  a  progressive  number  of  compounds  that  are  normally  excreted  by  kidneys  in  healthy  individuals.  Indoxylsulphate  (IXS)  and  p-cresylsulphate  (PCS), have  been  found  increased  in  subjects  with  end  stage  renal  disease  (ESRD)  creating  great  harm  to biological  systems;  these  uremic  toxins  come  from  the  intestinal  bacterial  fermentation  of  the  proteins.The aim of our study is to evaluate the short-term effects after an administration of pre / probiotics in CKD patients, regarding the production and then the serum concentrations of free IXS and PCS (i.e. non-protein bound fraction) and total IXS and PCS ( i.e. sum of unbound and protein bound fraction). Methods: In our study , 26 patients with CKD stage 2-5 associated with hypertension and / or diabetes mellitus type 2 were enrolled, and administered with 2 g/day dose of pre-probiotics for four months: mixed oligofructose  (prebiotic  component)  +  Lactobacillus  acidophilus  and  Bifidobacterium  longum (probiotic component). In all patients, at the beginning of the study, kidney function tests, glucose metabolism, PTH and blood uric acid were evaluated. Free and total PCS and IXS were also measured. 20 control subjects with normal renal function were considered in relation to the same parameters. After  4  months  19  patients  were  re-evaluated  in  relation  to  the  same  parameters.  Statistical  differences were studied using the Student-t paired and unpaired tests.